2022
DOI: 10.1172/jci161167
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID endotheliopathy: hypothesized mechanisms and potential therapeutic approaches

Abstract: SARS-CoV-2–infected individuals may suffer a multi–organ system disorder known as “long COVID” or post-acute sequelae of SARS-CoV-2 infection (PASC). There are no standard treatments, the pathophysiology is unknown, and incidence varies by clinical phenotype. Acute COVID-19 correlates with biomarkers of systemic inflammation, hypercoagulability, and comorbidities that are less prominent in PASC. Macrovessel thrombosis, a hallmark of acute COVID-19, is less frequent in PASC. Female sex at birth is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 147 publications
2
94
0
2
Order By: Relevance
“…In the meantime, changes in levels of D-dimer could serve as potential biomarkers of PCC to be used in routine practice, since D-dimers are a routine blood test, easy to perform and available in most settings. As showed in a recent review, there is growing understanding of a possible role of the endothelium in the pathophysiology of PCC 47 and, although the interpretation of abnormal D-dimer in this context has still to be elucidated, this may suggest the importance of closer follow-up of this subgroup of children or their participation in pharmacological trials, when available in pediatric practice. Importantly, elucidating the biological mechanisms responsible for sustained D‐dimer increases may be of relevance in PCC pathogenesis and has implications for clinical management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, changes in levels of D-dimer could serve as potential biomarkers of PCC to be used in routine practice, since D-dimers are a routine blood test, easy to perform and available in most settings. As showed in a recent review, there is growing understanding of a possible role of the endothelium in the pathophysiology of PCC 47 and, although the interpretation of abnormal D-dimer in this context has still to be elucidated, this may suggest the importance of closer follow-up of this subgroup of children or their participation in pharmacological trials, when available in pediatric practice. Importantly, elucidating the biological mechanisms responsible for sustained D‐dimer increases may be of relevance in PCC pathogenesis and has implications for clinical management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that viral S-proteins can be shed; are present in bodily fluids, microvessels, and tissues of SARS-CoV-2 infected patients; and can directly affect the vascular endothelium [ 12 , 21 , 22 , 23 , 24 ]. Evidence also suggests that long COVID-19 syndrome involves persistent microvascular endotheliopathy associated with increased SARS-CoV-2 virions and S-proteins in the blood and tissues as well as increased peripheral levels of pro-thrombotic factors [ 25 , 26 , 27 ]. In the present study, we investigate the direct and indirect effects of S-proteins’ exposure on expression and secretion of thrombogenic factors by primary human lung microvascular endothelial cells (HLMEC) and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the crucial role of endothelial dysfunction in the pathobiology of COVID-19, initially described by our research group [ 72 ] has been later confirmed by numerous investigators [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Indeed, endothelial cells have been shown to express the key co-factors involved for the internalization of SARS-CoV-2 in host cells, including angiotensin converting enzyme 2 (ACE2), transmembrane protease serine 2 (TMPRSS2), cathepsins B and D, TIM-1, neuropilin-1, and others, thereby representing a natural target of SARS-CoV-2 [ 83 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. Furthermore, the systemic inflammatory viral reaction observed in patients affected by COVID-19 has been shown to be linked to endothelial dysfunction [ 93 , 94 , 95 , 96 , 97 ], leading to thromboembolic events [ 98 , 99 , 100 ], which represent a common feature of COVID-19 cases with a severe outcome [ 101 , 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%